PENGARUH JOB-RELATED STRESS TERHADAP JOB SATISFACTION PADA PETUGAS PEMASYARAKATAN LEMBAGA PEMASYARAKATAN KELAS IIB NGAWI - Stevanus Adriano Kumayas; Padmono Wibowo (CV SWA Anugerah, 2023)
The purpose of this study is to determine the effect of job related stress on job satisfaction which ultimately affects employee performance and effectiveness. The research method used is to use a quantitative approach with a sample of 35 members, using a purposive sampling technique. The data collection method in this study was the Google form questionnaire method and the data was processed using SPSS 25. The results of job related stress research on job satisfaction in class IIB Ngawi correctional officers with a regression coefficient value of 0.842, which means the relationship between variables is a strong positive for the coefficient of determination it is known that the Job Related Stress variable explains the Job Satisfaction variable of 84.2% while the remaining 15.8% is explained by other variables